Ginsenoside Rg3 attenuates the osimertinib resistance by reducing the stemness of non‐small cell lung cancer cells. Issue 6 (9th January 2020) - Tan, Qinquan; Lin, Shunhuan; Zeng, Yihong; Yao, Mantian; Liu, Kejun; Yuan, Haiji; Liu, Chun; Jiang, Guanming
Abstract: In the present study, we found that Ginsenoside Rg3 attenuated the stemness of non‐small cell lung cancer (NSCLC) cells, evident by decreasing spheroid formation ability, ALDH1 activity and stemness marker expression. Furthermore, osimertinib‐resistant NSCLC cells displayed a stronger stemness than the parental cells. Ginsenoside Rg3 reduced the stemness and osimertinib resistance of osimertinib‐resistant cells. RNA‐sequencing revealed that Hippo signaling was shown on the top of the most upregulated pathways regulated by Ginsenoside Rg3 in NSCLC cells, and YAP/TAZ expression was suppressed by Ginsenoside Rg3. Notably, the inhibitor of Hippo signaling attenuated the effects of Ginsenoside Rg3 on the stemness of NSCLC cells. Therefore, Ginsenoside Rg3 attenuates the osimertinib resistance of NSCLC cells via suppressing the stemness, which is dependent on Hippo pathway.